Dietary brewer’s spent yeast enhances growth, hematological parameters, and innate immune responses at reducing fishmeal concentration in the diet of climbing perch, Anabas testudineus fingerlings - Gokulakrishnan, M.; Kumar, Rajesh; Pillai, Bindu R.; Nanda, S.; Bhuyan, S. K.; Kumari, Rakhi; Debbarma, Jackson; Ferosekhan, S.; Siddaiah, G. M.; Sundaray, Jitendra Kumar (Frontiers in Nutrition, 2022)
A 60-day feeding trial was conducted to optimally reduce the fishmeal level in climbing perch (Anabas testudineus) fingerling diet using a dietary brewer's spent yeast biomass (BSY) based diet. In this study, five isonitrogenous (35% CP) and isocaloric (19.15 MJ/Kg) feeds were prepared by replacing 0 (BSY0), 25% (BSY25), 50% (BSY50), 75% (BSY75) and 100% (BSY100) of fishmeal protein using BSY protein. A total of 225 numbers of uniform-sized climbing perch fingerlings (3.29 ± 0.09g) were randomly stocked in the 15 rectangular FRP (Fiber-reinforced plastic) tanks (150 L capacity). The experimental fish were fed twice daily at 4% BW for the first fortnight and later reduced to 3% BW based on satiation. At the end of the feeding trial, the weight gain (WG) of fish increased with the increasing BSY incorporation rates corresponding to fishmeal content and peaked at 77.88%, and beyond that, WG decreased. Food conversion ratios decreased as dietary BSY levels increased and peaked at 76.28%. All other growth and feed utilization parameters followed a similar trend of weight gain. Hepatosomatic index (HSI) and viscerosomatic index (VSI), A:G ratio, serum catalase activity, and monocytes were unaffected and the total serum protein, albumin, globulin, alanine aminotransferase (ALT), aspartate aminotransferase (AST), respiratory burst activity, lysozyme levels, myeloperoxidase activity, hemoglobulin, red blood cells, white blood cells, neutrophils, eosinophils, lymphocytes, and gut protease activities were increased significantly (P<0.05) with the increasing replacement levels and peaked between 25-75%. The serum SOD activity and total platelets were decreased, whereas the serum uric acid and gut amylase activities were increased significantly to the increasing levels of FM replacement in the diets (P<0.05). Among treatments, the BSY100 resulted in an overall poor growth response combined with relatively reduced values in nearly all biochemical parameters. The whole-body composition was nearly unaffected. The integrated biomarker response of various biochemical indicators from the different treatments has shown that the 50% fishmeal protein can be optimally replaced by BSY, which would cause an 18% reduction in the Economic conversion ratio (ECR) and -270.28 gCO2e- reduction in carbon footprint value per kg of climbing perch fingerlings production.